THEORETICAL AND METHODOLOGICAL APPROACHES TO INVESTMENT EVALUATION TO PROTECT THE ENVIRONMENT - LABENKO, Oleksandr; KLYMENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article clarifies that the volume of capital investment increase in environmental protection directly depends on financing due to depreciation and retained earnings, as well as on the attraction of private financial resources. The components of expenses for environmental protection have been studied, including: capital investments and current expenses.The concepts “capital investments in environmental protection”, “ecological investments”, “ecologically-oriented investments” and “nature-reproducing investments” have been summarized. The main sources of financing investments in environmental protection have been investigated. It has been found that, according to statistical data, the assessment of capital investments in environmental protection includes the analysis of: atmospheric air protection and climate change problems; treatment of return water; waste management; protection and rehabilitation of soil, underground and surface waters; other measures. The evaluation of the level of investments in environmental protection efficiency, which is carried out according to indicators for the analyzed period, has been provided. The volumes of capital investments and current costs for environmental protection in the processing industry of Ukraine for 2017-2021 have been analyzed. The share of costs for environmental protection at the expense of state and local budgets for 2017-2021 has been analyzed. It has been determined that the planning of the activities of industrial enterprises is carried out within the framework of the developed Target Program for the greening of production in any region of Ukraine, as coordinated, complex actions within the territorial and production entities allow to reduce the anthropogenic load on the surrounding natural environment.It has been established that among the most relevant options for greening the production of industrial enterprises are the following: modernization of treatment equipment and treatment facilities, introduction of low-waste and zero-waste innovative technologies into production. It has been established that in order to approve options for greening the production of domestic industrial enterprises, a preliminary analysis of their feasibility is first carried out by the method of expert evaluations according to parameters.
Keywords: capital investment; natural environment; protection; current costs; industrial enterprise; region; resources